Character Education in Junior High Schools: Teachers' Perceptions and Implementation Challenges - Syahbudin; Darnawati; Irawaty; Abubakar, Sitti Rahmaniar; Mustar, Sri Yuliani (Indonesian Values and Character Education Journal, 2024)
Character education in Junior High Schools (SMP) is an essential element in shaping students' strong personalities and noble character. However, in its implementation, there are various challenges faced by teachers, particularly related to understanding, skills, and support for the program. This study aims to analyze how SMP teachers perceive the implementation of character education in their schools and the challenges that arise in its development. The research method used is descriptive qualitative, with 30 SMP teachers as the subjects of the study. Data collection techniques included questionnaires, interviews, and documentation. The collected data were analyzed descriptively and presented in the form of tables and frequency distributions. The results of the study show that the majority of teachers, 93.31%, have a positive perspective on the implementation of character education in SMP. However, although the implementation is already good, there is still room for improvement in achieving more optimal outcomes. Therefore, it can be concluded that character education has been well implemented, but further socialization and training for teachers regarding mastery of technology and information are necessary to optimally support the character education program.